Synthesis of a sex pheromone of the longtailed mealybug, pseudococcus longispinus - Kurhade, Suresh E.; Siddaiah, V.; Bhuniya, Debnath; Reddy, D. Srinivasa (Synthesis-Stuttgart, 2013)
The synthesis of a recently identified and highly active sex pheromone of the longtailed mealybug, Pseudococcus longispinus is reported. A concise synthetic route, use of the under explored Meyer-Schuster rearrangement, Claisen rearrangement, and ring-closing metathesis are the highlights of this work.
Keywords: Acylation; Metathesis; pheromones; rearrangement; Total synthesis

Revisiting classical pummerer cyclization reaction: a key strategy for the synthesis of (+/-)-quinagolide - Chavan, Subhash P.; Kawale, Sanket A.; Tripathi, Anupam; Kadam, Appasaheb L.; Gonnade, Rajesh G. (ChemistrySelect, 2022)
A formal synthesis of (+/-)-quinagolide using beta-alanine as a starting material has been achieved. Late stage intramolecular classical Pummerer reaction has been used as a key synthetic tool to construct octahydrobenzo[g]quinoline skeleton of quinagolide. Conjugative reduction of olefin, regioselective C-alkylation over O-alkylation of beta-ketoester followed by retro-Dieckmann/ Dieckmann reaction sequence has been used as a key reaction sequence to achieve prerequisite sulfoxide for the Pummerer reaction. While revisiting the classical Pummerer reaction, the one-pot sequential thionium ion induced cyclocarbamation followed by N-carbamate deprotection and Friedel-Crafts type Pummerer cyclization was observed as an important finding of the present work.
Keywords: Alkylation; Cyclocarbamation; Hyperprolactinemia; rearrangement; Thionium ion

FeCl2-catalyzed rearrangement of aryl peroxyoxindole into 1,3-benzooxazin-4-One - Mohanta, Nirmala; Samal, PragnyaParamita; Krishnamurty, Sailaja; Gnanaprakasam, Boopathy (Advanced Synthesis & Catalysis, 2023)
We report an FeCl2-catalyzed radical rearrangement of aryl peroxyoxindoles into 1,3-benzooxazin-2-ones to obtain a variety of aryl substituted 1,3-benzooxazin-4-ones in moderate to good yields. Mechanistically, this skeletal rearrangement of peroxyoxindoles proceeded via radical pathway and was well supported with a series of experimental findings and DFT studies.
Keywords: 1; 3-Benzooxazin-4-one; FeCl2; Peroxyoxindole; rearrangement; Ring expansion

Accessing meta -enone-substituted anisoles using ArN 2 BF 4 as precatalyst via rearrangement of alkyne-tethered cyclohexadienones - Rai, Archana; Das, Utpal (Synthesis-Stuttgart, 2024)
Keywords: alkyne-tethered cyclohexadienone; diazonium salt; rearrangement; substituted anisoles